MULTIPLICATION RATE OF DIFFERENT POTATO CULTIVARS IN NW PLAINS OF INDIA FOR NUCLENS AND BREEDER SEED - Singh, D. B.; Singh, B. P.; Singh, O. P.; Ramkishore, Ramkishore; Singh, Rajpal; Singh, Sarjeet (Potato Journal, 2013)
The rate of multiplication of seed potato in stage-I ranged between 12.9 to 27.2 tubers per plant. Out of 7 varieties, Kufri Anand and Kufri Pukhraj produced the high number of tubers per plant ( 27.2) in stage-I. The rate of multiplication of these varieties in stage-II was 15.1 to 18.5 tubers per plant. Similarly the weight-wise multiplication rate of these potato cultivar was 5.0 to 6.0 times in stage-III and 4.9 to 6.6 in stage-IV.